EL OTRO CUSCO: CHOQUEQUIRAO - Apaza Huamani, John (2017)
The Inka society was established under a hierarchical but also nuclearized organization, the Inka always thought of a beginning, but not only mental, historical, but spatially or territorially, the system of ceques and the most important ritual of the Inka state was Qhapaq Qocha, A demonstration of how important everything should be, the zero point. So what does Cusco mean? There are several etymological analyzes in this regard, however the analysis must go from the perspective of the Cusco concept, in the mind of Inka society. Some chronicles, although not clearly related to the subject, have touched in their stories the idea that the Inka would construct New Cusco, which would imply not to the construction to urban and architectural similarity, but rather conceptual, clear that under the Criterion of an ideal spatial axis.